Design and manufacturing optimization of herbal drink crystallization machine using reverse engineering method - Santoso, Heru Agus; Islahudin, Nur; Wijaya, Dewa Kusuma (OPSI, 2023)
This article explains the design and manufacture of a herbal drink powder crystallization machine at Menik Jaya MSMEs. The problem with this research stems from the large number of defective products produced in the form of herbal powder that is burnt and lumpy. This is because production staff still manually stir the process continuously without stopping, causing fatigue due to work and impacting the quality of the process. So that the optimal design and manufacture of the crystallization machine is obtained where the dimensions of the machine are 130 cm high, 100 cm long and wide, machine legs height is 62 cm, stove height is 87 cm from the base and the stove pan handle width is 12 cm. Regarding engine performance, the ideal electric capacity of the motor is 60 watts with a stirrer and pan made from a combination of wood and AISI 3195 stainless steel. The pully uses 2 types of sizes, if the volume of raw material is small then a 4 cm pully is used with 10 Rpm rotation speed and 0,052 Nm torque value, while for large volumes a 6 cm pully is used with 15 Rpm rotation speed and 0,038 Nm torque value.